Interdisciplinary Communication in the Hospital Setting: A Systematic Review and Thematic Synthesis of the Qualitative Literature. (26th March 2021) - Gleeson, L; O'Brien, G L; O'Mahony, D; Byrne, S
Abstract: Introduction: Communication is widely recognised to play a key role in patient care. The US Institute of Medicine's 2002 report, ' Crossing the Quality Chasm', stated that ' effective methods of communication, both among caregivers and between caregivers and patients, are critical to providing high-quality care '.(1) Interdisciplinary communication (IDC) can be challenging due to differences in training, education and roles between healthcare professions. Due to the nature of IDC, the majority of research on this subject has been qualitative, exploring the views of healthcare professionals on IPC. To date, however, the qualitative evidence on IDC has not been synthesised in a systematic manner. Therefore, a systematic review of the qualitative literature on healthcare providers' experiences of interprofessional communication was conducted and registered with PROSPERO (registration number CRD42020177967). Aim: The primary aim of this systematic review was to synthesise the qualitative evidence regarding healthcare providers' perceptions of IDC in the hospital setting. A secondary aim was to identify the barriers and facilitators to IDC in the hospital setting. Methods: Studies were eligible for inclusion in the review if they met the following criteria: 1) studies examining healthcare professionals' experiences of IDC, 2) studies conducted in the hospital setting, and 3) studies conducted using qualitative research methods. Four databases (PubMed, CINAHL, Web of Science and Embase) were searched from inception until May 2020. Quality appraisal of the identified studies was conducted using the Critical Appraisal Skills Programme (CASP) tool for qualitative research. Data from the results sections of eligible studies were synthesised using thematic synthesis as described by Thomas and Harden.(2) Thematic synthesis consists of three stages: 1) line-by-line coding of all text relevant labelled ' results' or ' findings' in the included studies, 2) organisation of codes into descriptive themes that reflect the results of the included studies, and 3) development of descriptive themes into analytical themes that address the review question. Results: Eighteen studies were identified as being eligible for inclusion in this review (Figure 1). Five descriptive themes emerged during thematic synthesis: 1) 'Hierarchy', 2) ' Interprofessional Ethos', 3) 'Healthcare Environment', 4) ' Personal Factors' and 5) ' Methods of Communication', which were developed into two analytical themes: ' Barriers to IDC ' and 'Facilitators to IDC '. Personal factors, such as strong interprofessional relationships, were found to facilitate IDC, while organisational factors, such as challenging and hierarchical working environments, were found to pose barriers to IPC. Conclusion: We believe that this review makes a significant contribution to the literature. To our knowledge, it is the first study to synthesis the qualitative evidence on healthcare providers' perceptions of IDC in hospitals. Maintaining an interprofessional ethos and building positive working relationships were identified as facilitators to IDC, while hierarchy and challenging working conditions were identified as barriers. A key finding is the significance that healthcare providers associate with personal aspects of IDC, such as mutual respect and understanding among healthcare professionals. Future research should involve the theory- and evidence-driven design of interventions to improve personal aspects of IDC, such as interprofessional education and engagement. References: 1. Institute of Medicine. Crossing the Quality Chasm: A New Health System for the 21st Century - Institute of Medicine. Institute of Medicine. 2001. 2. Thomas J, Harden A. Methods for the thematic synthesis of qualitative research in systematic reviews. BMC Med Res Methodol. 2008;8(45).